Mitophagy in Traumatic Brain Injury: A New Target for Therapeutic Intervention. (27th January 2022) - Zhu, Mingrui; Huang, Xinqi; Shan, Haiyan; Zhang, Mingyang
Abstract : Traumatic brain injury (TBI) contributes to death, and disability worldwide more than any other traumatic insult and damage to cellular components including mitochondria leads to the impairment of cellular functions and brain function. In neurons, mitophagy, autophagy-mediated degradation of damaged mitochondria, is a key process in cellular quality control including mitochondrial homeostasis and energy supply and plays a fundamental role in neuronal survival and health. Conversely, defective mitophagy leads to the accumulation of damaged mitochondria and cellular dysfunction, contributing to inflammation, oxidative stress, and neuronal cell death. Therefore, an extensive characterization of mitophagy-related protective mechanisms, taking into account the complex mechanisms by which each molecular player is connected to the others, may provide a rationale for the development of new therapeutic strategies in TBI patients. Here, we discuss the contribution of defective mitophagy in TBI, and the underlying molecular mechanisms of mitophagy in inflammation, oxidative stress, and neuronal cell death highlight novel therapeutics based on newly discovered mitophagy-inducing strategies.